Engineered Mott ground state in a LaTiO3+δ/LaNiO3 heterostructure - Yanwei Cao (Nature Portfolio, 2016)
Interfaces between two dissimilar transition metal oxides can exhibit emergent strongly correlated electronic and magnetic states due to charge transfer and electronic reconfiguration. Here, the authors synthesize and investigate an exotic Mott ground state in LaTiO3+δ/LaNiO3heterostructures.